1990
DOI: 10.1007/bf01331354
|View full text |Cite
|
Sign up to set email alerts
|

On the role of stress-induced migration on time-dependent terminal velocities of falling spheres

Abstract: Abstract." There is experimental evidence to suggest that even under steady-state conditions the velocity of solid spheres or bubbles moving through viscoelastic fluids can become time dependent. One of the possible explanations offered for interpreting this phenomenon has been the generation of a polymer depleted layer in the line of passage Of the particles, which disappears due to the counterbalancing effect of molecular diffusion in the long range. We have done some careful experiments and measured these c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

1991
1991
2009
2009

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…The axisymmetric interaction results in a substantial acceleration of the trailing particle as was earlier observed for the solid spheres interacting in Carbopol solutions (Gheissary and van den Brule, 1996;Hariharaputhiran et al, 1998) as well as in other non-Newtonian fluids (Ambeskar and Mashelkar, 1990). As a result, two equal-size drops tend to approach each other and coalesce.…”
Section: Conclusion and Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…The axisymmetric interaction results in a substantial acceleration of the trailing particle as was earlier observed for the solid spheres interacting in Carbopol solutions (Gheissary and van den Brule, 1996;Hariharaputhiran et al, 1998) as well as in other non-Newtonian fluids (Ambeskar and Mashelkar, 1990). As a result, two equal-size drops tend to approach each other and coalesce.…”
Section: Conclusion and Discussionmentioning
confidence: 71%
“…This is in contrast to a wide range of non-Newtonian fluids without yield stress, where wake effects are relaxed at much shorter relaxation time (see, e.g. Ambeskar and Mashelkar, 1990, for a comprehensive review). Hariharaputhiran et al (1998) reported on the variation in the steady settling velocity of spheres with a time interval between experiments in a 0.3 wt% aqueous Carbopol-941 dispersion.…”
Section: Introductionmentioning
confidence: 96%
“…nomenon was also observed in the sedimentation of spheres through viscoelastic fluids (Ambeskar and Mashelkar, 1990). In these experiments, long-lasting effects (from minutes to several hours) were observed for fluids with relaxation times on the order of several seconds.…”
Section: Paa Solutionsmentioning
confidence: 94%
“…Bissgaard, Cho et al ., and Ambeskar and Mashelkar conducted experiments wherein they dropped spheres in aqueous PAM solutions. They measured the terminal settling velocities of these spheres and showed that the settling velocities of identical spheres, dropped consecutively along the same path in a PAM solution, kept increasing until a saturation velocity was reached.…”
Section: Introductionmentioning
confidence: 99%